Peran Pendidikan Dan Pekerjaan Ibu Dalam Konsumsi Sayur Anak Prasekolah - Ali Rosidi; Enik Sulistyowati (Universitas Muhammadiyah Semarang, 2012)
Less consumption of vegetables can lead to a deficiency of one or more vitamins and minerals. Food habits in children from past experience gained. Food consumption in children dependent on mother or family, especially maternal education and maternal employment. This study aims to determine the relationship between maternal education and maternalemployment with vegetable consumption in preschoolers.Research conducted at TK Budi Mulya Semarang. The design study was crosssectional. The dependent variable was a preschooler vegetable consumption and the independent variable were maternal education and maternal employment. Samples were 63 preschoolers.Most of mothers are high school educated is 54.0% and 65.1% of them had no job. Deficiency of vegetable consumption in children is 85.7% . No relationship between maternal education and maternal employment with vegetable consumption in preschoolers. Need to increase vegetable consumption in preschoolers by choosing a cheaper vegetables.Keywords : vegetable consumption, maternal education, maternal employment.